Effects of protein–DNA complex formation on the intermolecular vibrational density of states of interfacial water. Issue 11 (25th February 2016) - Chakraborty, Kaushik; Bandyopadhyay, Sanjoy
Abstract : The formation of a protein–DNA complex influences the transverse and longitudinal degrees of freedom of surrounding water in a nonuniform manner. Abstract : Single-stranded DNAs (ss-DNAs) are formed as intermediates during DNA metabolic processes. ss-DNA binding (SSB) proteins specifically bind to the single-stranded segments of the DNA and protect it from being degraded. We have performed room temperature molecular dynamics simulations of the aqueous solution of two DNA binding K homology (KH) domains (KH3 and KH4) of the far upstream element (FUSE) binding protein (FBP) complexed with two ss-DNA oligomers. Efforts have been made to explore the influence of complex formation on low-frequency vibrational density of states of the surface water molecules. It is revealed that increased back scattering of water confined around the complexed structures leads to significant blue shifts of the band corresponding to the O⋯O⋯O bending or restricted transverse motions of water, the effect being more for the bridged water molecules. Importantly, it is demonstrated that the formation of such complexed structures of a similar type may often influence the transverse and longitudinal degrees of freedom of the surrounding water molecules in a nonuniform manner.